2015
DOI: 10.1097/dbp.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Late Diagnosis of Autism Spectrum Disorder After Initial Negative Assessment by a Multidisciplinary Team

Abstract: Subsequent late diagnosis of ASD after an initial ASD-negative comprehensive assessment is a common clinical experience. Reasons for this scenario may include evolving diagnosis as well as missed and overdiagnosed cases of ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 13 publications
4
77
0
Order By: Relevance
“…At age 7, however, their ADI and ADOS scores were high and adaptive behaviour was low, similar to the “Stable diagnosis” group, despite having high‐average intelligence (Table S2). A similar pattern of findings has been reported for later‐diagnosed high‐risk children [Brian et al, ] and in clinical samples [Davidovitch, Levit‐Binnun, Golan & Manning‐Courtney, ]. The “Later diagnosed” subgroup also had high ADHD scores and the highest anxiety scores at 7 (Table S2).…”
Section: Discussionsupporting
confidence: 82%
“…At age 7, however, their ADI and ADOS scores were high and adaptive behaviour was low, similar to the “Stable diagnosis” group, despite having high‐average intelligence (Table S2). A similar pattern of findings has been reported for later‐diagnosed high‐risk children [Brian et al, ] and in clinical samples [Davidovitch, Levit‐Binnun, Golan & Manning‐Courtney, ]. The “Later diagnosed” subgroup also had high ADHD scores and the highest anxiety scores at 7 (Table S2).…”
Section: Discussionsupporting
confidence: 82%
“…Another limitation relates to age of diagnosis. While diagnoses made at age 2 years are relatively stable over time (Lord et al., ; Shen et al., ), there is variability associated with ASD onset and we expect that diagnostic status will change for a small proportion our sample as they age (Davidovitch, Levit‐Binnun, Golan, & Manning‐Courtney, ; Ozonoff et al., ). Whether the pattern of results observed here will generalize across a wider age range is an important issue, and we are currently following‐up participants from the present study at school‐age to account for later childhood outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to our findings, Frenette et al (2011) reported that in children with a diagnosis of ADHD, attention and hyperactivity symptoms masked core ASD symptoms and could explain why they were diagnosed 1.29 years later than those without ADHD. Further, Davidovitch et al (2015) reported that almost half of children later diagnosed with ASD were initially diagnosed with ADHD features and behaviors problems. The potential “masking effect” of ADHD symptoms on the diagnosis of ASD may lead clinicians to consider primarily a diagnosis of ADHD instead of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Some co-occurring conditions/symptoms can mask or modify the expression of the core ASD symptoms, which may result in later age of diagnosis or loss of a previous diagnosis (Blumberg et al 2016; Close et al 2012; Davidovitch et al 2015; Jonsdottir et al 2011; Levy et al 2010; Mandell et al 2007; Mazurek et al 2014; Wiggins et al 2012; Wu et al 2016). For example, Davidovitch et al (2015) found that children with language or cognitive deficits, or attention or motor problems were more likely to be diagnosed with ASD after the age of 6 years, even though they were initially evaluated at a younger age. A current or past developmental condition (e.g., developmental delay, hearing problem) or other disorders, such as anxiety or epilepsy, was associated with a loss of a previous ASD diagnosis (Close et al 2012).…”
Section: Introductionmentioning
confidence: 99%